Alternative of solution through the use of flexible barriers to geodynamic problems Cerro La Picota - Ayacucho - Peru - Escalante Contreras, Jorge (2019)
The present research work has the purpose of preventing the fatal risk to the inhabitants of the city of Ayacucho, who inhabit basically in the Cerro la Picota and the urban zone that is in the lower part, where it is observed seven ravines with various forms, gradients, slopes and coverages, which were formed by cyclical rainfall. Therefore, it causes a risk to the population by the transportation of debris, water and mud flows that causes damages in all its route, for which the application of flexible barriers is proposed, because the geodynamic, geomorphological and geotechnical reality requires it. There will be installed 22 flexible barriers, of which 04 are U-shaped greater than fifteen meters and 18 are V-shaped smaller than fifteen meters. In the first Puca Puca stream, one U-shaped and one V-shaped one will be installed; in the second stream San Martin Extension, two U-shaped and three V-shaped ones will be installed; in the third Upper Peru ravine, three V-shaped ones will be installed; in the fourth Yanaccacca creek, four V-shaped ones will be installed; in the fifth creek Prolongación Basilio Auqui, one will be installed in the form of a U and one in the form of V; in the sixth Piscotambo ravine, two V-shaped ones will be installed; in the seventh Accohuaycco creek, four V-shaped ones will be installed.